PENGARUH BIMBINGAN KELOMPOK TERHADAP KEPERCAYAAN DIRI PESERTA DIDIK KELAS X SMA NEGERI 5 PONTIANAK - Audia, Olga; Asrori, M.; Lestari, Sri (Jurnal Pendidikan dan Pembelajaran Khatulistiwa, 2018)
AbstractGroup guidance services are a process of providing assistance provided to individuals to help students solve problems and achieve optimal development conducted in groups. The better the implementation of group guidance services the higher the confidence level of learnersTherefore, the researcher wanted to know more about how big the influence of group guidance service to the students' self confidence X class SMA Negeri 5 Pontianak. The general problem of this research is "How much influence the guidance service group to the confidence of students Class X SMA Negeri 5 Pontianak ?." The method used is a descriptive method with a quantitative approach that is the problem-solving procedure by describing the influence distribution of group guidance services to confidence students class X SMA Negeri 5 Pontianak. While data collecting technique used is indirect communication technique. The form of this study is the study of relationships. Collection tools used are questionnaires and inventory.Â Â Keyword: self confidence, descriftive method